Aplikasi Kontrol Barang Habis Pakai Berbasis Web sebagai Solusi Manajemen Inventaris - Riski Annisa; Panny Agustia Rahayuningsih; Anna Anna (J-INTECH ( Journal of Information and Technology), 2024)
Inventory management is an important element for agencies as physical economic resources whose existence and maintenance are needed to support the smooth work process. At the Kubu Raya BAPPEDA Office, administrative activities involving the use of consumables are still carried out conventionally, so they are prone to file damage and data loss due to paper-based manual recording. This research aims to overcome these problems by developing a web-based consumable control application that can manage data on goods, employees, requests, rooms, users, incoming transactions, incoming goods reports, and handover of goods pick-up. The research method uses a waterfall software development model, supported by the CodeIgniter framework and MySQL database. The result is an innovative application that enables centralized, automated, and real-time data management by all parts of the organization. The main advantages of this application over conventional systems are its ability to reduce the risk of data loss, improve recording efficiency, and simplify the reporting process. It also supports more transparent and accurate inventory management, while reducing the time it takes to process requests and report consumables. Thus, this application has a real impact in increasing the efficiency and effectiveness of goods management in the government agency environment.